The Art of Adaptation in Film and Video Games - Thomas, Christian (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Arts explores the art and practice of adaptation in several different mediums with a focus on film and video games. The topics covered include experimental game design, narrative design, film and trauma, games adapted from literature, video game cinema, film and the pandemic, film and the environment, film and immigration, and film and culture.